Cidadania e gestão fiscal: a efetividade da lei de responsabilidade fiscal no âmbito do tribunal de contas da união - Mont'Alverne, Marcelo de Miranda (2007)
The present work has for objective to analyze the effectiveness of the Law of Fiscal Responsibility in the scope of the Court Accounts of the Union, being verified if the attitudes of this agency are apt to restrain actions of agent against principal to the budgetary balance, planning, transparency and fiscalization, being objectified the construction of the fiscal Citizenship. One examines the concept of citizenship and its relation with a responsible fiscal management, as well as the historical factors that had conditioned the sprouting of the Law of Fiscal Responsibility, considered vital instrument for the honest of the public finances. This study it still consists of an ample doctrinal research detaching the objectives, aspects and excellent principies of the Law of Fiscal Responsibility whose objective is to balance the public accounts and to make responsible the public agents for the bad application of the public mounts of money in the scope of them legislative, Executive and Judiciary in all the leveis of the federacy. It is analyzed structure and abilities of the Court of Accounts of the Union, responsible agency for the countable control of the public finances, assisting the Legislative in its paper of fiscalization of the good financial management of the State, aiming at to clarify its importance for the fulfilment of the Law of Fiscal Responsibility. Finally, a jurisprudencial research next to the Court of Accounts of the Union was carried through, aiming at, through jurisprudenciais data, to clarify if its sanctions, having for bedding Complementary Law n. 101/2000, are capable to restrain practical harmful to the common wealth.